Developmental changes induced by exogenous testosterone during early phases of prostate organogenesis - Ramos, Jordana Gomes; Assis Silva, Joao Paulo de; Manso, Luana Araujo; Rodrigues, Giovanna Amaral; Taboga, Sebastiao Roberto [UNESP]; Carvalho, Hernandes Faustino de; Alcantara dos Santos, Fernanda Cristina; Biancardi, Manoel Francisco (Elsevier B.V., 2020)
The aim of this study was to evaluate the impact of prenatal testosterone exposure on prostate development in male and female neonatal gerbils. Pregnant females were exposed to subcutaneous injections of testosterone cypionate (500 mu g/animal) at gestational days 20 and 22. Male and female pups were then euthanized at postnatal day 1. Morphological analysis showed that females were severely affected by androgen exposure. We also observed that male and female urogenital sinus (UGS) responded differentially to testosterone treatment, demonstrating heterogeneous immunostaining for the androgen receptor (AR), estrogen receptor alpha (ER alpha), and proliferating cell nuclear antigen (PCNA). Smooth muscle alpha-actin (alpha-SMA) analysis showed that testosterone delays the myodifferentiation, allowing buds to reach the ectopic mesenchymes of the female UGS. Our data showed that abnormal testosterone exposure disrupted prostate organogenesis, altered the expression patterns of important markers, and demonstrated that female UGS was particularly influenced by androgen exposure during a critical window in the developmental period.
Keywords: Testosterone; Development; Prostate; Masculinization; Sexual dimorphism; Gerbils